Dampak Perubahan Iklim Global terhadap Kerentanan Sosial Ekonomi Masyarakat Pesisir di Maluku - Pelu, Fadli (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to analyze the socio-economic vulnerability of coastal communities in Maluku in facing the impacts of global climate change. The coastal areas of Maluku, where most of the population relies on the traditional fisheries sector, face major challenges due to global warming, sea level rise, and changes in oceanographic parameters such as temperature, salinity, pH, and ocean currents. These changes have a significant impact on marine ecosystems, especially coral reefs and fisheries habitats, which ultimately affect the livelihoods and welfare of coastal communities. In addition to ecological challenges, communities also face socio-economic constraints such as low education, limited access to basic services, and weak local institutions. Therefore, ecosystem-based adaptation and mitigation strategies, community empowerment, and strengthening institutional capacity are important to increase the resilience of coastal communities in Maluku to climate change. This study recommends the need for a cross-sectoral collaborative approach and integration of local knowledge in the formulation of sustainable coastal development policies.